2010
DOI: 10.7763/ijesd.2010.v1.68
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Waste Age on Landfill Leachate Quality

Abstract: The influence of waste age on the characteristic of leachate from a landfill site where young and mature waste cells were investigated over a period of six years to evaluate the impact of waste age on quality of leachate generated. Results of the study revealed that the leachate quality is affected by waste age due to its impacts to bacterial growth and chemical reaction in the waste mass of landfill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 11 publications
(5 reference statements)
1
23
0
1
Order By: Relevance
“…Cortez et al (2010a) reported that, in leachate from an old landfill located in Portugal, COD and BOD 5 were as low as 743 and 10 mg/L. Similarly, Lee et al (2010) found that, in old leachate, the mean concentrations of COD, BOD 5 and…”
Section: Characteristics Of Landfill Leachatementioning
confidence: 96%
“…Cortez et al (2010a) reported that, in leachate from an old landfill located in Portugal, COD and BOD 5 were as low as 743 and 10 mg/L. Similarly, Lee et al (2010) found that, in old leachate, the mean concentrations of COD, BOD 5 and…”
Section: Characteristics Of Landfill Leachatementioning
confidence: 96%
“…It is also believed that ammonia is mainly released during the organic matter decomposition (Burton and Watson-Craik 1998). Thus ammonia appears to be a good indicator for organic nitrogen in the leachate (Lee et al 2010). The piggery wastewater has not contained nitrate nitrogen because it was taken soon after its generation and without preliminary treatment.…”
Section: Landfill Leachatementioning
confidence: 99%
“…Due to the high concentration of contaminants, advanced technological treatments are required to reach the prescribed emission standards (Liu et al, 2015). A major concern is related to the qualitative changes which leachate undergoes over time during the landfill management phases (Kulikowska and Klimiuk, 2008;Lee et al, 2010). Young leachates with high BOD/ COD ratio, high ammonium content and low pH can be successfully treated by means of biological treatment, while alternative treatments are used for the old leachates characterized by a significant fraction of recalcitrant compounds (humic acid, fulvic acid) and a high ionic strength (Stegmann and Ehrig, 1981;Cossu et al, 1992;Renou et al, 2008).…”
Section: Introductionmentioning
confidence: 99%